Functional outcome of the treatment of AO-ASIF type C distal humerus fracture using Lambda plate - Bista, Krishna Bahadur; Shrestha, Rabeendra Prasad; Shrestha, Bhola; Kandel, Ishwar Sharma; Dakal, Rabi Mohan (Journal of Gandaki Medical College-Nepal, 2020)
Introduction: Although the use of two plates for the treatment of type-C distal humerus fracture is popular, site of plate placement still is under debate. Use of Lambda plate for the fracture treatment can be easier and settle the dispute. This study aims to evaluate the functional outcome of the surgery using Lambda Plate. This can be a reference for surgeons and helps them make the decision about choice of implant for type C distal humerus fracture treatment among Nepalese people. Methods: This interventional study used Lambda plate for the treatment of type C fracture of distal humerus. Patients were examined at 4, 12, and 24 weeks respectively for the measurement of the outcome. Visual analogous scale was used for assessment of pain, range of motion for functional recovery and Mayo Elbow Performance Score was used for the assessment of functional outcome. Paired-samples t-test and linear regression was used to for data analysis. Results: Functional outcome at the last follow-up was excellent in 24(53.33%) patients, good in 18(40%) patients and fair in 3(6.67%) patients. Range of motion of elbow increased significantly with every follow-up (p-value <0.001). Average angle of flexion at last follow-up was 117.53°±11.74 while loss of extension was 7.53°±4.86. Average number of patients had their fracture union at 19.84±2.38 weeks. There was no association of age, sex and union weeks with functional outcome when measured with MEPS. Conclusion: Fixation of distal humerus fracture by using Lambda plate gave excellent and satisfying outcome in terms of pain, range of motion and objective functional outcome.